1999
DOI: 10.1128/jcm.37.12.4120-4123.1999
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Salmonella by Using Selenite Brilliant Green Sulfa Enrichment Broth

Abstract: The efficacy and sensitivity of selenite brilliant green sulfa enrichment (SBG) broth for the isolation of Salmonella from fecal specimens were evaluated by using both clinical and artificially infected (artificial) fecal specimens. An examination of 1,588 clinical fecal specimens found Salmonella in 296 specimens, including 89 cases detected by the direct-plating xylose-lysine-desoxycholate method and an additional 207 cases detected after enrichment with SBG broth. Therefore, the recovery ofSalmonella with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The number of Salmonella increased up to (7.3±0.2) log CFU/chicken, followed by TSB media [(7.1±0.4) log CFU/chicken]. The result of this study was in good agreement with the result of Boer(17), which demonstrated that BHI and TSB exhibited significantly greater increases than other non-selective media. However, there were no significant differences among the media until 4 hr (p<0.05).Unlike other media, the number of Salmonella enriched in SC did not increase obviously between 2 hr and 4 hr.…”
supporting
confidence: 86%
“…The number of Salmonella increased up to (7.3±0.2) log CFU/chicken, followed by TSB media [(7.1±0.4) log CFU/chicken]. The result of this study was in good agreement with the result of Boer(17), which demonstrated that BHI and TSB exhibited significantly greater increases than other non-selective media. However, there were no significant differences among the media until 4 hr (p<0.05).Unlike other media, the number of Salmonella enriched in SC did not increase obviously between 2 hr and 4 hr.…”
supporting
confidence: 86%
“…Milk and soft cheese samples were added to an enrichment media and then incubated at 36±1°C for 24 h for the further investigation. To identify the pathogen, different enrichment media were used as follow: Trypticase Soy Broth (TSB) for Escherichia coli O157:H7 (Lye et al 2013); Baird-Parker Agar Base for Staphylococcus aureus (Rahimi and Alian 2013); Listeria Enrichment Broth Base for Listeria monocytogenes (Amagliani et al 2006); and selenite brilliant green sulfa enrichment (SBG) broth for Salmonella enterica serovar Typhimurium (Chang et al 1999).…”
Section: Microbial Enrichmentmentioning
confidence: 99%
“…(USDA, 2019). Hektoen Enteric (HE) agar inhibits gram‐positive bacteria and differentiates Salmonella using bile salts, bromothymol blue, and acid fuchsin dyes to produce blue to blue‐green colonies with a black center (Chang et al, 1999; Goo, Ching, & Gooch, 1973; King et al, 2005; Kristensen, Lester, & Jürgens, 1925).…”
Section: Introductionmentioning
confidence: 99%